PENULIS PEREMPUAN DAN LOKALITAS DALAM RUBRIK CERPEN JAWA POS TAHUN 2021 - Arisandi, Isep Bayu (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
This paper is based on short stories by women writers in Jawa Pos in 2021. The problem discussed is the element of locality in the short story. Five short stories became the object of analysis to find the locality setting and locality elements in the short story. The descriptive analysis method is used to find locality in the setting and narrative of the short story. Data from each short story is described to obtain an overview of the short story's background and locality elements. The results of the analysis show that the real place setting is a reflection of the locality identity in the short story. The real place setting in the short story becomes the opening gate for the locality theme, thus establishing a link between the structure and the short story theme. The locality presented by the 5 short stories refers to the forms of tradition, myth, and historical elements. Tradition, myth, and historical elements are tied to the setting of places and events in the short story. This analysis shows that an important real setting is built in a short story that has a locality narrative.